Sistem Pendukung Keputusan Penentuan Kelayakan Nasabah Penerima Pinjaman pada Koperasi Menggunakan Metode MOORA - Gilbert Johan Martin Sinaga; William Charlie Septian Sinaga (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2026)
Savings and loan cooperatives face challenges in determining the eligibility of loan applicants objectively, which may increase the risk of non-performing loans. This study aims to develop a decision support system for assessing the eligibility of cooperative loan applicants using the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method. The study utilizes secondary data from 30 applicants evaluated based on six criteria: monthly income, loan amount, credit history, loan period, collateral, and employment status. The MOORA method is applied through decision matrix construction, normalization, weighting, optimization value calculation, and alternative ranking, and is subsequently implemented in a web-based decision support system. The results indicate that the MOORA method is capable of producing objective and measurable eligibility rankings and classifying applicants into eligibility categories. The developed system can assist cooperatives in improving the accuracy and consistency of loan decision-making.